EFEKTIVITAS GAME EDUKASI “MELADA” UNTUK MENINGKATKAN KETERAMPILAN BERNYANYI LAGU DAERAH - Salsabilla, Nathania Hellen; Zulfikasari, Sony (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning regional songs in elementary schools faces major challenges due to the massive dominance of popular digital culture and conventional, text-based learning methods, which cause low student motivation and skills. This study aims to examine the effectiveness of using the "MELADA" (Mengenal Lagu Daerah) Educational Game as an interactive learning medium to improve regional song singing skills among third-grade students at SD Negeri Sudirman Ambarawa. A quantitative approach with a quasi-experimental method and a nonequivalent control group design was applied. The research sample consisted of 60 students, divided into an experimental class (3A, n=27) using the "MELADA" game and a control class (3B, n=26) using conventional methods. Data were collected using skala linkert-based pretests and posttests, evaluated through four structured singing indicators. Data analysis was performed using the Wilcoxon Signed Rank test, Mann-Whitney U test, and N-Gain calculation through SPSS 25. The results showed that the experimental class experienced a significant increase, with the average score rising from 28.04 to 70.22, achieving an average N-Gain score of 0.92 (92%), which falls into the "High" and "Effective" categories. In contrast, the control class only increased from 29.58 to 37.19, with an N-Gain of 0.56 (56% or "Moderately Effective"). The Mann-Whitney U test confirmed a highly significant difference between the two groups (U=0, p=0.000). Thus, the "MELADA" educational game is proven to be highly effective and is recommended as an innovative solution to enhance regional song singing skills in elementary education.